Pengembangan Media PowerPoint Berdasarkan Teori Kognitif untuk Mahasiswa Pendidikan Agama Islam - arief ardiansyah (Vicratina : Jurnal Ilmiah Keagamaan, 2018)
The development of information and communication technology gives a big impact on the joints of education. This is clearly seen in the use of computer technology in learning. By using computer technology, a teacher can utilize multimedia-based learning. The term that refers to the use of computer technology for learning is called E-learning. The use of E-learning that is commonly used in classrooms is the use of PowerPoint presentations. However, to be able to utilize these media effectively in learning must be based on an appropriate learning theory. One of them is the application of the principles of cognitive learning theory in the design of Powerpoint media. Some of these principles include applying multimedia principles, applying the principle of contiguity, applying the principle of modality, and applying the principle of coherence. Kata kunci: pengembangan media powerpoint, teori kognitif, mahasiswa pendidikan agama islam.